Risk Management In The Flood Control Project Of Tukad Unda, Klungkung Regency - I Ketut Mahardika Putra; Ni Kadek Sri Ebtha Yuni; Luh Putu Prativi Putri Suardika (Universitas Pendidikan Nasional, 2026)
The Tukad Unda Flood Control Project was implemented to support river normalization and spatial planning efforts aimed at reducing flood risks in Klungkung Regency. However, the project faces significant challenges due to its location in flood-prone, swamp, and coastal areas, which increase the likelihood of risks during construction. This study aims to identify potential project risks, assess risk acceptance levels, develop appropriate mitigation strategies, and allocate risk ownership among stakeholders. A mixed-method approach combining quantitative and qualitative descriptive analysis was employed. Primary data were collected through surveys and group discussions, while secondary data were obtained from relevant literature. Respondents were selected using purposive sampling based on their professional roles and experience in the project, representing owners, consultants, and contractors. A total of 37 risk variables were identified and analyzed using validity and reliability tests to ensure data consistency. The results indicate four levels of risk acceptance: unacceptable (2.70%), undesirable (37.84%), acceptable (37.84%), and negligible (21.62%). Fifteen dominant risks were identified, requiring mitigation through risk avoidance and risk reduction strategies. These findings highlight the importance of experience-based risk assessment in improving the effectiveness of construction project management.